PERAN BUDAYA ORGANISASI DALAM MEMEDIASI PENGARUH GAYAKEPEMIMPINAN DAN ETIKA TERHADAP KINERJA PERUSAHAN - Deni Risianto; Dodi W. Irawanto; Mugiono Mugiono (MIX: JURNAL ILMIAH MANAJEMEN, 2018)
Abstract: The purpose of this study was to tested and explained empirically about (1)the effect of leadership style on the organizational performance, (2) the effect of ethicon the organizational performance, (3) the effect of leadership style on theorganizational performance through organizational culture, and 4) the effect of ethicalon organizational performance through organizational culture. The sample was takenusing the sample proportion method. The selected respondents were employees of PTWidatra Bhakti who have worked for more than 2 years. In this case the researcher tooka sample of 174 respondents. The research hypothesis was tested using Partial LeastSquare (PLS) analysis technique. The results of this study indicated that leadershipstyle and ethics did not give a direct influence on organizational performance.Organizational culture had a role in mediated the effect of leadership and ethical styleson organizational performance. Thus the role of organizational culture had an importantrole in producing performance in the organization.